2015
DOI: 10.1016/j.str.2015.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Tubulation by Amphiphysin Requires Concentration-Dependent Switching from Wedging to Scaffolding

Abstract: Summary BAR proteins are involved in a variety of membrane remodeling events, but how they can mold membranes into different shapes remains poorly understood. Using EPR, we find that vesicle binding of the N-BAR protein amphiphysin is predominantly mediated by the shallow insertion of amphipathic N-terminal helices. In contrast, the interaction with tubes involves deeply inserted N-terminal helices together with the concave surface of the BAR domain, which acts as a scaffold. Combined with the observed concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
89
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(95 citation statements)
references
References 61 publications
6
89
0
Order By: Relevance
“…What might be the mechanistic basis for this? N-BAR proteins such as amphiphysin and endophilin contain an N-terminal amphipathic ␣-helix (H0) that inserts into membranes and facilitates the anchoring of BAR domains to membranes (54)(55)(56). Some other BAR domain proteins harbor a lipid-binding domain such as the pleckstrin homology (PH) domain, which is important for membrane binding and the generation of membrane curvature (47,57).…”
Section: Discussionmentioning
confidence: 99%
“…What might be the mechanistic basis for this? N-BAR proteins such as amphiphysin and endophilin contain an N-terminal amphipathic ␣-helix (H0) that inserts into membranes and facilitates the anchoring of BAR domains to membranes (54)(55)(56). Some other BAR domain proteins harbor a lipid-binding domain such as the pleckstrin homology (PH) domain, which is important for membrane binding and the generation of membrane curvature (47,57).…”
Section: Discussionmentioning
confidence: 99%
“…By using electron paramagnetic resonance, it has recently been revealed that N-BAR domains differently bind spherical than cylindrical membranes [56,57]. On a spherical membrane, binding is primarily mediated by the helices while, on a membrane nanotube, the BAR domain more tightly adheres on the surface.…”
Section: Discussionmentioning
confidence: 99%
“…The surface density of proteins and the size of the vesicles are individually measured with total internal reflection microscopy, allowing a measure of the curvature-induced sorting with very good precision [55]. This measure is a priori complementary to the sorting deduced from nanotube experiments, but it is possible that the geometry of the membrane might influence how anisotropic proteins (such as BAR domains) bind to the surface, ultimately affecting their sorting [56,57].…”
Section: (D) Small Liposomesmentioning
confidence: 99%
“…Some of the BAR superfamily proteins, such as N-BAR proteins, also have hydrophobic insertions. Experimentally, the membrane tubulation and curvaturesensing by various types of BAR superfamily proteins have been observed [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%